Bulk-Fill composite restorations step-by-step description of clinical restorative techniques case reports = Restauraciones compuestas Bulk-Fill descripción paso a paso de las técnicas de restauración clínica informes de casos - Vasconcelos Monteiro, Renata
Composite resins are excellent materials for direct restorations in the posterior region, satisfactorily reestablishing esthetics and function. Recently, a new class of composites has been commercialized, the so-called Bulk-fill resins. These resins may be inserted in the dental cavity in increments of 4 to 5 mm thick, and have the advantages of reducing polymerization shrinkage and clinical working time. The aim of this case report was to describe the use of bulk-fill composite resins to restore Class I and Class II cavities by means of two different restorative techniques.